Copper metal covalent organic framework material, composite membrane material, and preparation method and application of copper metal covalent organic framework material and composite membrane material

By designing copper metal covalent organic frame material (Cu-COF) blended with polymer to prepare composite film materials and used in triboelectric nanogenerators, the shortcomings of existing TENG in transmission and cycling performance are solved, and flexibility is achieved High output performance and long cycle stability of Cu-COF@MC TENG devices.

CN119490634APending Publication Date: 2025-02-21ZHONGYUAN ENGINEERING COLLEGE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410859579.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-06-28
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

Existing triboelectric nanogenerators (TENGs) have little research on transmission performance and cycling performance, and it is difficult to meet the high-performance needs of self-powered sensors.

Method used

Design a copper metal covalent organic frame material (Cu-COF) to prepare composite film material by blending it with polymer and using it for triboelectric nanogenerators to design flexible Cu-COF@MC TENG devices .

Benefits of technology

It realizes the good output performance and excellent cycle stability of Cu-COF@MC TENG devices, and can maintain efficient operation at high frequencies and long-term times. It is suitable for self-powered human body sensors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119490634A_ABST
    Figure CN119490634A_ABST
Patent Text Reader

Abstract

The invention discloses a copper metal covalent organic framework material (Cu-COF), a composite film material and a preparation method and application of the composite film material. The preparation method comprises the following steps: carrying out Schiff base reaction on tri (2-4 formaldehyde-pyrazole nitrogen-N, N ')-tri-copper and 2, 5-dimethoxy terephthaloyl hydrazine to construct a crystal material Cu-COF; cu-COF and MC are compounded to prepare flexible Cu-COF and MC composite film materials with different proportions, and a Cu-COF-TENG device is assembled, so that the TENG device assembled by 10% of Cu-COF and MC has optimal output performance and excellent stability. Then, a flexible TENG capable of being pressed / pressed continuously of a Cu-COF-MC-TENG device is constructed, a TENG signing motion monitoring self-powered sensor is analyzed, and contact and separation of the TENG are achieved under the condition that a sign pen moves, so that mechanical energy is converted into an electric signal, and application in a Cu-COF flexible sensor is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of friction nanogenerators, and in particular to a copper metal covalent organic framework material, a composite film material, and a preparation method and application thereof. Background Art

[0002] The development of electronic devices that use clean energy (such as wind, solar, water and distributed mechanical energy) can provide a new way to solve the inherent shortcomings of traditional energy technologies. Wang Zhonglin's team first built a triboelectric nanogenerator (TENG) triboelectric nanogenerator (TENG) structural design and related application research, (2014.3 student Zhang Hulin, instructor Professor Hu Chenguo, deputy instructor Academician Wang Zhonglin, Chongqing University doctoral dissertation); it can generate electrical energy from the surrounding mechanical energy (including wind, vibration, water and human activities). Triboelectric nanogenerators have attracted increasing research attention due to their low cost, easy manufacturing, high output power and high conversion efficiency. In the past few years, researchers in this field have made a lot of efforts to improve the performance of TENG to meet its wide application in powering microelectronic devices and self-powered sensors, such as selecting suitable friction materials, controlling morphology and structural optimization. Triboelectric nanogenerators (TENG) have great potential in the field of self-powered sensor manufacturing. Recently, smart electronic devices and motion monitoring sensors have attracted the attention of scientists due to their applications in the field of artificial intelligence. This flexible self-powered sensor has potential application prospects in artificial intelligence and robotics manufacturing.

[0003] Covalent organic frameworks (COFs) are a unique class of crystalline porous materials constructed from organic building blocks through reversible chemical reactions. Since the pioneering work reported by Yaghi and colleagues in 2005, great progress has been made in the exploration of topological maps and synthetic reactions in the past decade. Benefiting from the characteristics of designable regular porous structures and multifunctional functions designed through topology and building blocks, COFs are considered to be one of the most promising materials for gas adsorption and separation, sensing, ion conductors, catalysis, energy storage, semiconductors, and electronic devices. In addition, another advantage of COFs is their densely arranged p-columns and arrays on the skeleton, which can be used as pre-arranged pathways to facilitate charge transport. This distinct feature is difficult to achieve with other inorganic and organic materials. Therefore, COFs can provide an attractive structure-function platform for the development of suitable TENG systems. In addition, most of the triboelectric materials used in TENGs are based on polymers, mainly due to the flexibility, smoothness and strong charging ability of polymers. A large amount of evidence shows that the functional group characteristics and chemical structure of polymers can determine the performance of TENG.

[0004] Triboelectric nanogenerators (TENGs) provide a simple and effective method for collecting low-frequency mechanical energy. TENGs combined with the human body can collect biomechanical energy and convert it into electrical signals through basic working modes to monitor human activities. At present, great progress has been made in the application of TENGs in motion sensing, human-machine interface, and medical care. However, the transmission performance and cycle performance are less studied. Summary of the invention

[0005] In view of the technical problems existing in the prior art, the present invention proposes a copper metal covalent organic framework material, a composite film material and a preparation method and application thereof. By designing a metal organic framework material and using it to prepare a composite film material, and using the composite film material for a triboelectric nanogenerator, a flexible Cu-COF@MC TENG device is designed, which shows good output performance and excellent cycle stability, and can be better applied to related self-powered human body sensor materials.

[0006] In order to achieve the above object, the technical solution of the present invention is achieved as follows:

[0007] A copper metal covalent organic framework material, wherein the molecular structure of the copper metal covalent organic framework material (Cu-COF) is as shown in formula (I), wherein "---" represents an omitted repeating unit:

[0008]

[0009] The method for preparing the copper metal covalent organic framework material comprises the following steps: (1) uniformly dispersing 1H-pyrazole-4-carboxaldehyde and copper salt in a first solvent, heating and reacting, separating, washing and precipitating; and then drying to obtain tris(2-4-carboxaldehyde-pyrazole nitrogen-N, N′)-tricopper;

[0010] The reaction formula for preparing tris(2-4-formaldehyde-pyrazole nitrogen-N,N′)-tricopper is shown in (II):

[0011]

[0012] In the formula, Cu n X m Represents copper salt.

[0013] (2) uniformly dispersing the tris(2-4-formaldehyde-pyrazolyl-N,N′)-tricopper and 2,5-dimethoxyterephthaloylhydrazide obtained in step (2) in a second solvent, performing a Schiff base reaction, rapidly freezing in liquid nitrogen, degassing by freeze-pump-thaw cycle, sealing the reaction container, and then heating for reaction;

[0014] The reaction formula for generating Cu-COF is shown in (III):

[0015]

[0016] (3) The copper metal covalent organic framework material Cu-COF is obtained by centrifuging, washing and drying the reaction product.

[0017] In the step (1), the copper salt is copper nitrate, copper chloride, copper sulfate or a hydrate thereof; the molar ratio of 1H-pyrazole-4-carboxaldehyde to the copper salt is 1:(0.5-1.2); the first solvent is a mixed solvent of N,N-dimethylacetamide, anhydrous ethanol and deionized water, and the volume ratio of N,N-dimethylacetamide, anhydrous ethanol and deionized water is (1-1.5):(1-1.5):1; the total volume of the solvent is 15-20 mL / mmol based on the molar ratio of 1H-pyrazole-4-carboxaldehyde.

[0018] The temperature of the heating reaction in step (1) is 80-120° C., and the reaction time is 10-14 h. The separation washing is centrifugal washing, first centrifugally washing with water and anhydrous ethanol; then soaking in water for three days to remove excess copper ions, and finally washing with anhydrous ethanol and drying.

[0019] In the step (2), the molar ratio of tris(2-4-formaldehyde-pyrazole nitrogen-N,N′)-tricopper and 2,5-dimethoxyterephthaloyl hydrazide is 1:(1-1.5); the second solvent is a mixed solution of mesitylene, dioxane and acetic acid aqueous solution; the volume ratio of mesitylene, dioxane and acetic acid aqueous solution is (3-8):(3-8):1, and the molar concentration of the acetic acid aqueous solution is 4-8 mol / L; the temperature of the heating reaction is 100-150° C., and the time is 60-84 h.

[0020] The method of washing and drying in step (3) is washing with anhydrous THF, methanol and deionized water respectively, and then drying under vacuum. The vacuum drying temperature is 60-80° C. and the time is 60-84 hours.

[0021] A composite membrane material based on a copper metal covalent organic framework material is prepared by dissolving and blending a polymer with the above-mentioned copper metal covalent organic framework material or the copper metal covalent organic framework material prepared by the above-mentioned method under the action of a solvent, and casting the composite membrane material based on the copper metal covalent organic framework material.

[0022] The polymer includes methyl cellulose, and the solvent includes DMF; in the composite membrane material, the copper metal covalent organic framework material accounts for 1-20wt% of the composite membrane material based on the copper metal covalent organic framework material;

[0023] Preferably, the copper metal covalent organic framework material accounts for 5-15wt% of the composite film material based on the copper metal covalent organic framework material;

[0024] More preferably, the copper metal covalent organic framework material accounts for 10 wt % of the copper metal covalent organic framework material-based composite film material.

[0025] A friction nanogenerator comprises electrodes, two friction materials, a supporting structure and an external circuit; the friction material comprises the above-mentioned composite film material based on copper metal covalent organic framework material.

[0026] The friction nanogenerator is of contact-separation type, horizontal sliding type, single-electrode type or independent friction layer type.

[0027] The present invention has the following beneficial effects:

[0028] 1. The present invention obtains a copper-based covalent organic framework material through a unique molecular structure design, which combines the metal nodes in metal organic frameworks (MOFs) and the covalently bonded organic linking units in COFs. The obtained Cu-COF has the following characteristics: high crystallinity, porosity, structural diversity, stability, electronic conductivity or catalytic activity, and electrical conductivity. The preparation method of the material is simple, and it has the advantages of organic framework materials and the electrical conductivity of electronic conduction.

[0029] 2. The Cu-COF of the present invention is obtained by a commonly used solvent thermal reaction method. Combining Cu-COF with TENG provides a new option for the development of TENG materials, while broadening the range of friction layer material selection and the application field of COF materials.

[0030] 3. The Cu-COF crystal material in the present invention has good stability and remains stable below 290°C ( Figure 3 ), and can maintain the intact morphology of the Cu-COF@MC composite film during the entire collision process, laying the foundation for continuous use. And it can maintain long-term cycle stability of up to 30,000 working cycles at an impact frequency of 5 Hz.

[0031] 4. The Cu-COF crystal material designed by the present invention has good stability and remains stable below 290°C; the crystalline porous material with highly ordered characteristics can accurately establish the structure-performance relationship and provide guidance for the design of high-performance triboelectric materials. The uniform metal nodes and high porosity in the porous crystal material promote more charge transfer and storage.

[0032] 5. In the present invention, the surface potential, roughness and dielectric constant of the polymer composite material can be improved by doping Cu-COFs, and it can be used as a triboelectric material, especially the Cu-COF@MC-TENG device with 10wt% Cu-COF added, which can be a flexible TENG that can be pressed / pressed continuously. The TENG finger signature motion monitoring self-powered sensor is analyzed. When the signature pen moves, the TENG realizes contact and separation, thereby converting mechanical energy into electrical signals. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0034] Figure 1 This is the X-ray powder diffraction pattern of the Cu-COF material obtained in Example 1.

[0035] Figure 2 This is the solid NMR analysis diagram of the Cu-COF material obtained in Example 1.

[0036] Figure 3 This is the thermogravimetric analysis diagram of the Cu-COF material obtained in Example 1.

[0037] Figure 4 The nitrogen absorption curve and pore size distribution diagram of the Cu-COF material obtained in Example 1.

[0038] Figure 5 This is the FT-IR spectrum analysis diagram of the Cu-COF material obtained in Example 1.

[0039] Figure 6 This is the current diagram of the Cu-COF@MC-TENG device obtained in Examples 7-11 at an impact frequency of 5 Hz.

[0040] Figure 7 This is the voltage diagram of the Cu-COF@MC-TENG device obtained in Example 7-11 at an impact frequency of 5 Hz.

[0041] Figure 8 This is the power density diagram of the 10% Cu-COF@MC-TENG device obtained in Example 9 at an impact frequency of 5 Hz.

[0042] Fig. 9 This is the current diagram of the 10% Cu-COF@MC-TENG device obtained in Example 9 at different impact frequencies.

[0043] Fig.10 This is the voltage diagram of the 10% Cu-COF@MC-TENG device obtained in Example 9 at different impact frequencies.

[0044] Fig.11 This is a graph of the cyclic stability of the current of the 10% Cu-COF@MC-TENG device obtained in Example 9 at an impact frequency of 5 Hz.

[0045] Fig.12 This is a graph of the cyclic stability of the voltage of the 10% Cu-COF@MC-TENG device obtained in Example 9 at an impact frequency of 5 Hz.

[0046] Fig.13 This is a real picture of the 10% Cu-COF@MC-TENG flexible sensor device obtained in Example 9 tested at an impact frequency of 5 Hz.

[0047] Fig.14 This is a test result diagram of writing the word SOS on the 10% Cu-COF@MC-TENG flexible sensor device obtained in Example 9 at an impact frequency of 5 Hz.

[0048] Fig.15 This is a test result diagram of writing the word HELP on the 10% Cu-COF@MC-TENG flexible sensor device obtained in Example 9 at an impact frequency of 5 Hz. DETAILED DESCRIPTION

[0049] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0050] Example 1

[0051] The preparation method of the Cu-COF material of this embodiment comprises the following steps:

[0052] 1. Synthesis of Cu monomer

[0053] (1) 1H-pyrazole-4-carboxaldehyde (HPyCA) (0.096 g, 1.0 mmol), copper nitrate trihydrate (Cu(NO 3 ) 2 .3H 2 O) (0.20 g, 0.83 mmol), N,N-dimethylacetamide (DMF) (6.7 mL), anhydrous ethanol (EtOH) (6.7 mL), and deionized water (5 mL) were placed in a reaction kettle respectively;

[0054] (2) placing the reactor in step (1) in an oven at 100° C. and reacting for 12 h;

[0055] (3) After the reaction, separation is performed, and washing is performed with water and anhydrous ethanol to obtain a yellow solid;

[0056] (4) placing the yellow solid in step (3) into a centrifuge tube and adding water, changing the water three times a day for a total of three days;

[0057] (5) Three days later, the yellow solid in step (4) was washed with water and anhydrous ethanol, and then placed in an oven at 70° C. and taken out after 5 hours to prepare tris(2-4-formaldehyde-pyrazole nitrogen-N, N′)-tricopper[(Cu 3 (PyCA)3.H 2 O)];

[0058] 2. Preparation of Cu-COF materials

[0059] (1) Tris(2-4-formaldehyde-pyrazole nitrogen-N,N′)-tricopper[(Cu 3 (PyCA)3.H 2 O)] and 2,5-dimethoxyterephthaloylhydrazide (C 10 H 14 N 4 O 4 ) and a solvent are loaded into a Pyrex tube; the molar ratio of the two is 1:1.2; the reaction solvent is mesitylene, dioxane and acetic acid aqueous solution, the volume ratio of the three is 5:5:1, and the molar concentration of the acetic acid aqueous solution is 6 mol / L;

[0060] (2) the test tube was rapidly frozen in liquid nitrogen, degassed by freeze-pump-thaw cycles, the test tube was sealed, and then reacted in an oven at 120° C. for 3 days;

[0061] (3) The precipitate was collected by centrifugation, washed with anhydrous THF, methanol, and deionized water, respectively, and then dried at 70 °C under vacuum for 48 h to obtain Cu-COF powder, which combines the metal nodes in metal organic frameworks (MOFs) and the covalently bonded organic linking units in COFs;

[0062] The corresponding X-ray powder diffraction pattern is shown in Figure 1 As shown, the peak is sharp and the baseline is flat, indicating that the obtained Cu-COFs have high crystallinity;

[0063] Figure 2 The solid NMR analysis of the obtained Cu-COF shows that the Cu-COF crystal material has good crystallization, especially in Figure 2The binding energy of the C=N bond at position 3 is relatively high, which further confirms the formation of the imine bond in Cu-COF;

[0064] Figure 3 This is the thermogravimetric analysis diagram of the obtained Cu-COF, which shows that the Cu-COF crystal material has good thermal stability and remains stable below 290°C, providing a good performance foundation for its application in nano-friction generators.

[0065] Figure 4 The nitrogen absorption curve and pore size distribution of the obtained Cu-COF are shown in Figure 2. The BET surface area of ​​Cu-COF is 1000 m 2 g -1 and pore size of 3.35nm, which provides a good performance foundation for its application in nano friction generator.

[0066] Figure 5 This is the FT-IR spectrum analysis diagram of the obtained Cu-COF. From the diagram, it can be analyzed that the imine bond of Cu-COF has been synthesized.

[0067] Embodiment 2-6

[0068] The Cu-COF obtained in Example 1 and the polymer methyl cellulose were used to prepare a composite membrane, and the steps were as follows:

[0069] a. Take a suitable amount of the Cu-COF crystal powder material in Example 1;

[0070] b. Ultrasonic dispersion in 2 mL of DMF;

[0071] c. Weigh 400 mg of MC powder, add 6 mL of DMF, heat at 100 °C and stir for 30 min until completely dissolved, then transfer to room temperature;

[0072] d. Add the dispersed crystal powder to the dissolved MC and stir at room temperature for 4 hours;

[0073] e. Pour the dispersed mixed solution into a glass mold, cure at 80°C for 0.5h, cool and then demold to obtain a Cu-COF@MC composite film;

[0074] Example 2: Weigh 4.4 mg of the Cu-COF crystal powder material in Example 1 to obtain a 1% Cu-COF@MC composite film;

[0075] Example 3: Weigh 21 mg of the Cu-COF crystal powder material in Example 1 to obtain a 5% Cu-COF@MC composite film;

[0076] Example 4: Weigh 44 mg of the Cu-COF crystal powder material in Example 1 to obtain a 10% Cu-COF@MC composite film;

[0077] Example 5: Weigh 70.5 mg of the Cu-COF crystal powder material in Example 1 to obtain a 15% Cu-COF@MC composite film;

[0078] Example 6: 100 mg of the Cu-COF crystalline powder material in Example 1 was weighed to obtain a 20% Cu-COF@MC composite film.

[0079] Embodiment 7-11

[0080] The Cu-COF@MC TENG devices were assembled using the composite films obtained in Examples 2-6, corresponding to Examples 7-11, respectively, and the steps were as follows:

[0081] f. Cut the Cu-COF@MC films obtained in Examples 2-6 into 5×5 cm 2 , as a friction material and adhered to the sticky side of the electrode Cu tape; at the same time, a copper wire is adhered to the back of the copper tape as an external wire;

[0082] g. Use the spin-coated PVDF as another friction material, paste it on the supporting structure copper sheet, and cut it into 5×5cm 2 ; Paste copper wire on the back as another external conductor;

[0083] h. Assemble the Cu-COF@MC TENG devices with external circuits as given in f and g, respectively, corresponding to the Cu-COF@MC-TENG devices in proportions of 1%, 5%, 10%, 15% and 20% in Examples 7-11.

[0084] The obtained Cu-COF@MC-TENG devices with a ratio of 1%, 5%, 10%, 15% and 20% were tested at 5HZ, and the current values ​​obtained were 17.15μA, 30.01μA, 53.63μA, 43.85μA and 28.22μA, respectively (as shown in Figure 2). Figure 6 shown).

[0085] The obtained Cu-COF@MC-TENG devices with a ratio of 1%, 5%, 10%, 15% and 20% were tested at 5 Hz, and the voltage values ​​obtained were 322.1 V, 355.3 V, 536.7 V, 405.3 V and 363.0 V, respectively (as shown in Figure 2). Figure 7 shown).

[0086] The 10% Cu-COF@MC-TENG device obtained in Example 9 was tested at 5 Hz, and its maximum power density under different loads was 1326.5 mW / m 2 (like Figure 8 shown).

[0087] The cyclic stability test of the TENG device assembled with the 10% Cu-COF@MC composite film material obtained in Example 9 was carried out.

[0088] The 10% Cu-COF@EC-TENG device in Example 9 was continuously tested at 1 Hz, 2 Hz, 4 Hz, 6 Hz, and 8 Hz, and the current values ​​were obtained from 1 Hz to 8 Hz. As the impact frequency increased, the current became larger, which were 13.2 μA, 20.7 μA, 44.3 μA, 75.07 μA, 114.12 μA, respectively (as shown in Figure 5 ). Fig. 9 shown).

[0089] In Example 9, the 10% Cu-COF@MC-TENG device was continuously tested at 1Hz, 2Hz, 4Hz, 6Hz, and 8Hz, and the current values ​​were 361.1V, 415.5V, 447.5V, 549.0V, 593.7V (as shown in Figure 9) from 1Hz to 8Hz, as the impact frequency increases, the voltage increases. Fig.10 shown).

[0090] The 10% Cu-COF@MC-TENG device obtained in Example 9 was tested and the current value was 54.3 μA, with no obvious attenuation after 30,000 cycles (e.g. Fig.11 shown).

[0091] The 10% Cu-COF@MC-TENG device in Example 9 was continuously tested at 5 Hz, and the voltage value was 543.7 V, with no obvious attenuation after 30,000 cycles (e.g. Fig.12 shown).

[0092] The sensor test was completed using the 10% Cu-COF@MC-TENG flexible sensor device obtained in Example 9:

[0093] (1) The 10% Cu-COF@MC-TENG flexible device in Example 9 is connected to the friction nanogenerator. The actual connection diagram is shown in the figure ( Fig.13 shown);

[0094] (2) Test whether the waveform of the current is consistent with the letters when different letters are written on the flexible device at 5 Hz.

[0095] (3) The letters SOS were tested, and the waveform of the current was consistent with the written letters, showing the good performance of Cu-COF@MC-TENG as a flexible sensor device (such as Fig.14 shown).

[0096] (4) The letters HELP were tested, and the waveform of the current was consistent with the written letters, showing the good performance of Cu-COF@MC-TENG as a flexible sensor device (such as Fig.15 shown).

[0097] The Cu-COF doped with methyl cellulose (MC) of the present invention is used as a friction electrode material to prepare a composite film, and multiple groups of methyl cellulose (MC) composite films with different proportions are prepared to explore the output performance of the friction nanogenerator; on the other hand, Cu-COF is used as a flexible sensor material to achieve certain sensor performance.

[0098] Example 12

[0099] The preparation method of the Cu-COF material of this embodiment comprises the following steps:

[0100] 1. Synthesis of Cu monomer

[0101] (1) 1H-pyrazole-4-carboxaldehyde (HPyCA) (0.096 g, 1.0 mmol), copper nitrate trihydrate (Cu(NO 3 ) 2 .3H 2 O) (0.12 g, 0.5 mmol), N,N-dimethylacetamide (DMF) (5 mL), anhydrous ethanol (EtOH) (5 mL), and deionized water (5 mL) were placed in a reaction kettle respectively;

[0102] (2) placing the reactor in step (1) in an oven at 120° C. and reacting for 10 h;

[0103] (3) After the reaction, separation is performed, and washing is performed with water and anhydrous ethanol to obtain a yellow solid;

[0104] (4) placing the yellow solid in step (3) into a centrifuge tube and soaking it in water, changing the water three times a day for a total of three days;

[0105] (5) Three days later, the yellow solid in step (4) was washed with water and anhydrous ethanol, and then placed in an oven at 70° C. and taken out after 5 hours to prepare tris(2-4-formaldehyde-pyrazole nitrogen-N, N′)-tricopper[(Cu 3 (PyCA)3.H 2 O)];

[0106] 2. Preparation of Cu-COF materials

[0107] (1) Tris(2-4-formaldehyde-pyrazole nitrogen-N,N′)-tricopper[(Cu 3 (PyCA)3.H 2 O)] and 2,5-dimethoxyterephthaloylhydrazide (C10 H 14 N 4 O 4 ) and a solvent are loaded into a Pyrex tube; the molar ratio of the two is 1:1.5; the reaction solvent is mesitylene, dioxane and acetic acid aqueous solution, the volume ratio of the three is 3:8:1, and the molar concentration of the acetic acid aqueous solution is 4 mol / L;

[0108] (2) the test tube was rapidly frozen in liquid nitrogen, degassed by freeze-pump-thaw cycles, the test tube was sealed, and then reacted in an oven at 150° C. for 60 h;

[0109] (3) The precipitate was collected by centrifugation, washed with anhydrous THF, methanol, and deionized water, respectively, and then dried at 80 °C under vacuum for 60 h to obtain Cu-COF powder, which combines the metal nodes in metal-organic frameworks (MOFs) and the covalently bonded organic linking units in COFs.

[0110] Embodiment 13

[0111] The preparation method of the Cu-COF material of this embodiment comprises the following steps:

[0112] 1. Synthesis of Cu monomer

[0113] (1) 1H-pyrazole-4-carboxaldehyde (HPyCA) (0.096 g, 1.0 mmol), copper nitrate trihydrate (Cu(NO 3 ) 2 .3H 2 O) (0.29 g, 1.2 mmol), N,N-dimethylacetamide (DMF) (7.5 mL), anhydrous ethanol (EtOH) (7.5 mL), and deionized water (5 mL) were placed in a reaction kettle respectively;

[0114] (2) placing the reactor in step (1) in an oven at 80° C. and reacting for 14 h;

[0115] (3) After the reaction, separation is performed, and washing is performed with water and anhydrous ethanol to obtain a yellow solid;

[0116] (4) placing the yellow solid in step (3) into a centrifuge tube and soaking it in water, centrifuging and changing the water three times a day for a total of three days;

[0117] (5) Three days later, the yellow solid in step (4) was washed with water and anhydrous ethanol, and then placed in an oven at 70° C. and taken out after 5 hours to prepare tris(2-4-formaldehyde-pyrazole nitrogen-N, N′)-tricopper[(Cu 3 (PyCA)3.H 2 O)];

[0118] 2. Preparation of Cu-COF materials

[0119] (1) Tris(2-4-formaldehyde-pyrazole nitrogen-N,N′)-tricopper[(Cu 3 (PyCA)3.H 2 O)] and 2,5-dimethoxyterephthaloylhydrazide (C 10 H 14 N 4 O 4 ) and a solvent are loaded into a Pyrex tube; the molar ratio of the two is 1:1; the reaction solvent is mesitylene, dioxane and acetic acid aqueous solution, the volume ratio of the three is 8:3:1, and the molar concentration of the acetic acid aqueous solution is 8 mol / L;

[0120] (2) The test tube was quickly frozen in liquid nitrogen, degassed by freeze-pump-thaw cycle, the test tube was sealed, and then reacted in an oven at 100° C. for 84 h;

[0121] (3) The precipitate was collected by centrifugation, washed with anhydrous THF, methanol, and deionized water, respectively, and then dried at 60 °C under vacuum for 84 h to obtain Cu-COF powder, which combines the metal nodes in metal-organic frameworks (MOFs) and the covalently bonded organic linking units in COFs.

[0122] Embodiment 14

[0123] The Cu-COF obtained in Example 12 and the polymer methyl cellulose were used to prepare a composite membrane, and the steps were as follows:

[0124] a. Take 20 mg of the Cu-COF crystal powder material in Example 12;

[0125] b. Ultrasonic dispersion in 2 mL of DMF;

[0126] c. Weigh 400 mg of MC powder, add 6 mL of DMF, heat at 100 °C and stir for 30 min until completely dissolved, then transfer to room temperature;

[0127] d. Add the dispersed crystal powder to the dissolved MC and stir at room temperature for 4 hours;

[0128] e. The dispersed mixed solution was poured into a glass mold, cured at 80°C for 0.5h, and then cooled and demolded to obtain a Cu-COF@MC composite film; a 4.8% Cu-COF@MC composite film was obtained.

[0129] The Cu-COF@MC TENG device is assembled using the composite film of this embodiment, and the steps are as follows:

[0130] f. Cut the Cu-COF@MC film obtained in Example 12 into 5×5 cm 2 , as a friction material and adhered to the sticky side of the electrode Cu tape; at the same time, a copper wire is adhered to the back of the copper tape as an external wire;

[0131] g. Use the spin-coated PVDF as another friction material, paste it on the supporting structure copper sheet, and cut it into 5×5cm 2 ; Paste copper wire on the back as another external conductor;

[0132] h. Assemble the above f and g into Cu-COF@MC TENG devices with external circuits to obtain a Cu-COF@MC-TENG device with a ratio of 4.8%.

[0133] Embodiment 15

[0134] The Cu-COF obtained in Example 13 and the polymer methyl cellulose were used to prepare a composite membrane, and the steps were as follows:

[0135] a. Take 30 mg of the Cu-COF crystal powder material in Example 12;

[0136] b. Ultrasonic dispersion in 2 mL of DMF;

[0137] c. Weigh 400 mg of MC powder, add 6 mL of DMF, heat at 100 °C and stir for 30 min until completely dissolved, then transfer to room temperature;

[0138] d. Add the dispersed crystal powder to the dissolved MC and stir at room temperature for 4 hours;

[0139] e. The dispersed mixed solution was poured into a glass mold, cured at 80°C for 0.5h, and then cooled and demolded to obtain a Cu-COF@MC composite film; a 7.0% Cu-COF@MC composite film was obtained.

[0140] The Cu-COF@MC TENG device is assembled using the composite film of this embodiment, and the steps are as follows:

[0141] f. Cut the Cu-COF@MC film obtained in Example 12 into 5×5 cm 2 , as a friction material and adhered to the sticky side of the electrode Cu tape; at the same time, a copper wire is adhered to the back of the copper tape as an external wire;

[0142] g. Use the spin-coated PVDF as another friction material, paste it on the supporting structure copper sheet, and cut it into 5×5cm 2 ; Paste copper wire on the back as another external conductor;

[0143] h. Assemble the above f and g into Cu-COF@MC TENG devices with external circuits to obtain a Cu-COF@MC-TENG device with a ratio of 4.8%.

[0144] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A copper metal covalent organic framework material, characterized in that: The molecular structure of the copper metal covalent organic framework material is shown in formula (I), where "---" represents an omitted repeating structural unit:

2. The method for preparing the copper metal covalent organic framework material according to claim 1, characterized in that: The steps include: (1) uniformly dispersing 1H-pyrazole-4-carboxaldehyde and copper salt in a first solvent, heating and reacting, separating, washing and precipitating; and then drying to obtain tris(2-4-carboxaldehyde-pyrazole nitrogen-N,N′)-tricopper; (2) uniformly dispersing the tris(2-4-formaldehyde-pyrazolyl-N,N′)-tricopper and 2,5-dimethoxyterephthaloylhydrazide obtained in step (2) in a second solvent, rapidly freezing in liquid nitrogen, degassing by freeze-pump-thaw cycle, sealing the reaction vessel, and then heating for reaction; (3) preparing the copper metal covalent organic framework material of formula (I) by centrifuging, washing and drying the reaction product.

3. The method for preparing the copper metal covalent organic framework material according to claim 1, characterized in that: The copper salt in step (1) is copper nitrate, copper chloride, copper sulfate or a hydrate thereof; The ratio of the amount of 1H-pyrazole-4-carboxaldehyde to the copper salt is 1:(0.5-1.2); the first solvent is a mixed solvent of N,N-dimethylacetamide, anhydrous ethanol and deionized water, and the volume ratio of N,N-dimethylacetamide, anhydrous ethanol and deionized water is (1-1.5):(1-1.5):1; the total volume of the solvent is 15-20mL / mmol based on the amount of 1H-pyrazole-4-carboxaldehyde.

4. The method for preparing the copper metal covalent organic framework material according to claim 1, characterized in that: The temperature of the heating reaction in step (1) is 80-120° C., and the reaction time is 10-14 h. The separation and washing is suction filtration washing, first washing with water and / or ethanol; then soaking in water for three days to remove excess copper ions, and finally washing with anhydrous ethanol and drying.

5. The method for preparing the copper metal covalent organic framework material according to claim 1, characterized in that: In the step (2), the molar ratio of tris(2-4-formaldehyde-pyrazole nitrogen-N,N′)-tricopper and 2,5-dimethoxyterephthaloyl hydrazide is 1:(1-1.5); the second solvent is a mixed solution of mesitylene, dioxane and acetic acid aqueous solution; the volume ratio of mesitylene, dioxane and acetic acid aqueous solution is (3-8):(3-8):1, and the molar concentration of the acetic acid aqueous solution is 4-8 mol / L; the temperature of the heating reaction is 100-150° C., and the time is 60-84 h.

6. The method for preparing the copper metal covalent organic framework material according to claim 1, characterized in that: The method of washing and drying in step (3) is washing with anhydrous THF, methanol and deionized water respectively, and then drying under vacuum. The vacuum drying temperature is 60-80° C. and the time is 60-84 hours.

7. A composite membrane material based on copper metal covalent organic framework material, characterized in that: The polymer and the copper metal covalent organic framework material according to claim 1 are dissolved and blended under the action of a solvent, and then cast and dried to form a composite membrane material based on the copper metal covalent organic framework material.

8. The composite membrane material based on copper metal covalent organic framework material according to claim 7, characterized in that: The polymer includes methyl cellulose, and the solvent includes DMF; the copper metal covalent organic framework material accounts for 1-20wt% of the composite membrane material based on the copper metal covalent organic framework material.

9. A friction nanogenerator, characterized in that: The friction nanogenerator comprises electrodes, two friction materials, a supporting structure and an external circuit; the friction material comprises the composite film material based on the copper metal covalent organic framework material according to claim 7 or 8.

10. The triboelectric nanogenerator according to claim 9, characterized in that: The friction nanogenerator is of contact-separation type, horizontal sliding type, single-electrode type or independent friction layer type.